Productivity in the peanut under salt stress in soil with a cover of plant mulch - Castelo Sousa, Henderson; Vinícius de Araújo Viana, Thales; Gomes de Sousa, Geocleber; Moreira de Azevedo, Benito; Ingryd Nojosa Lessa, Carla; Márcio Henrique da Costa Freire, Márcio; Ferreira Goes, Geovana; Baldé, Bubabar (Revista Ciência Agronômica, 2023)
Peanut cultivation in the northeast of Brazil has been badly aff ected by salts accumulating in the irrigation water; inthis respect, the use of plant mulch is one way of mitigating salt stress. The aim of this study was to evaluate the eff ect of irrigationusing brackish water under diff erent mulching strategies on productivity and water use effi ciency in the peanut. The experiment wascarried out under fi eld conditions in Redenção, in the state of Ceará, in a randomised block design of split-plots with fi ve replications,in which the plots corresponded to two levels of electrical conductivity of the irrigation water (0.8 and 4.0 dS m-1), and the subplots tosix mulching strategies based on the phenology of the crop (MS1: mulch throughout the cycle; MS2: fl owering stage; MS3: appearanceof the gynophore; MS4: pod formation; MS5: fi nal fl owering stage; MS6: no mulch). The following were determined at the end ofthe experimental cycle: commercial, non-commercial and total number of pods, number of grains per pod, pod length and diameter,productivity and water use effi ciency. Irrigation with lower-salinity water, together with mulching during the phenological stages of thepeanut, aff ords better productive performance and greater water use effi ciency. Salt stress reduced the length and diameter of the pods andhad a negative eff ect on productivity and water use effi ciency, both with and without the use of plant mulch during the phenological stages.